Comprehensive splice-site analysis using comparative genomics - Sheth, Nihar (2012)
We have collected over half a million splice sites from five species—Homo sapiens, Mus musculus, Drosophila melanogaster, Caenorhabditis elegans and Arabidopsis thaliana—and classified them into four subtypes: U2-type GT–AG and GC–AG and U12-type GT–AG and AT–AC. We have also found new examples of rare splice-site categories, such as U12-type introns without canonical borders, and U2-dependent AT–AC introns. The splice-site sequences and several tools to explore them are available on a public website (SpliceRack). For the U12-type introns, we find several features conserved across species, as well as a clustering of these introns on genes. Using the information content of the splice-site motifs, and the phylogenetic distance between them, we identify: (i) a higher degree of conservation in the exonic portion of the U2-type splice sites in more complex organisms; (ii) conservation of exonic nucleotides for U12-type splice sites; (iii) divergent evolution of C.elegans 3′ splice sites (3′ss) and (iv) distinct evolutionary histories of 5′ and 3′ss. Our study proves that the identification of broad patterns in naturally-occurring splice sites, through the analysis of genomic datasets, provides mechanistic and evolutionary insights into pre-mRNA splicing.